The impact of happy and sad affective states on biases in ethical decision making. Issue 4 (19th May 2021) - Rainone, Nicolette A.; Watts, Logan L.; Mulhearn, Tyler J.; McIntosh, Tristan J.; Medeiros, Kelsey E.
ABSTRACT: Researchers have increasingly acknowledged that affect plays a role in ethical decision making. However, the impact that specific affective states may have on the expression of decision biases in the context of ethical dilemmas has received limited empirical attention. To address this, the present effort examined the impact of happy and sad affective states on biases in ethical decision making. In an online experiment, undergraduate students read short stories that either induced happy, sad, or relaxed (neutral) affective states, followed by a covert measure of three types of biases (i.e., simplification, verification, and regulation) held to inhibit ethical decision making. Results demonstrated that happy affective states increased the expression of regulation biases, and sad affective states increased the expression of simplification biases, compared to relaxed (neutral) affective states. Implications are discussed for advancing research on ethical decision making and reducing unethical behavior in organizations.